Principals' Perceptions Pertaining to the Policy Engagement of Driving Organizations (NGOs) in Advancing Education Quality: Curriculum Reform Study - Mustofa Mustofa; Kacung Marijan; Afib Rulyansah; Syamsul Ghufron (STAI Hubbulwathan Duri, 2023)
Non-governmental organizations (NGOs) have assumed a prominent role within the academic landscape of numerous countries. Recently, governmental authorities have granted authorization for NGOs to actively participate in augmenting the quality of educational endeavours. The present research aims to delve comprehensively into the perspectives of school principals regarding the active engagement of NGOs in elevating educational standards within the context of Indonesia. Employing qualitative research methods, the study conducted in-depth interviews with a cohort of five elementary school principals located in Surabaya. This investigative approach underscores the acknowledgment of a multifaceted, dynamic, and contextual reality, marked by inherent subjectivity and fluidity, intertwined within the socio-cultural and political milieu. Employing inductive processes, the research employs techniques of data condensation, encoding, categorization, and theorization to facilitate the analysis of the collected data. The resultant findings from this empirical inquiry have revealed the emergence of three overarching thematic constructs: firstly, the formulation of partnership policies involving driving organizations or NGOs; secondly, the cultivation of shared educational responsibilities; and lastly, the discernible benefits stemming from the active involvement of NGOs. The unfolding of an innovative model, borne out of the collaborative policy framework with NGOs, serves as a distinctive political and institutional approach that facilitates the orchestration of collective efforts. This model notably substantiates its efficacy in fostering mutually beneficial collaborations, thereby introducing novel paradigms, methodologies, and educational resources.